2017
DOI: 10.1186/s11671-017-2205-7
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Quantum Dots in Annealed GaAsBi/AlAs Quantum Wells

Abstract: Formation of bismuth nanocrystals in GaAsBi layers grown by molecular beam epitaxy at 330 °C substrate temperature and post-growth annealed at 750 °C is reported. Superlattices containing alternating 10 nm-thick GaAsBi and AlAs layers were grown on semi-insulating GaAs substrate. AlAs layers have served as diffusion barriers for Bi atoms, and the size of the nanoclusters which nucleated after sample annealing was correlating with the thickness of the bismide layers. Energy-dispersive spectroscopy and Raman sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Crystalline structure was also investigated using high‐resolution X‐Ray diffractometer Rigaku SmartLab. Photoluminescence measurements of the annealed GaAsBi/AlAs MQW demonstrated quantum confinement effects attributed to the Bi QDs …”
Section: Methodssupporting
confidence: 55%
See 3 more Smart Citations
“…Crystalline structure was also investigated using high‐resolution X‐Ray diffractometer Rigaku SmartLab. Photoluminescence measurements of the annealed GaAsBi/AlAs MQW demonstrated quantum confinement effects attributed to the Bi QDs …”
Section: Methodssupporting
confidence: 55%
“…An obvious correlation between the size of QDs and the width of QW layers can be traced in the image. In our previous study, [7] we have qualitatively shown the feasibility of QD size control by changing QW's thickness. In this study, a large array (20 MQW's) of uniform QW's was grown in order to accurately quantify the distribution of sizes (%1500 Bi QD's in total).…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, anti-sites, where the group III or V sites have an element from the other site, as has also been seen in GaAs(Bi) [32,33], may increase the observed lattice mismatch. We speculate that it is also possible that in InGaAsBi, bismuth gives rise to inhomogeneities leading to the formation of clusters or other localised structures in the layer similar to that observed in GaAsBi [20,34,35,36]. Additionally, observations of surface roughness from the SEM images ( Fig.…”
Section: Rbs Channelling Measurementsmentioning
confidence: 70%